Persepsi Petani terhadap Peran Petugas Penyuluhan Pertanian dalam Tahapan Penerapan Inovasi Pupuk Organik (Studi di Desa Ulapato B Kecamatan Telaga Biru Kabupaten Gorontalo) - Sintia Damayanti; Zulham Sirajuddin; Karlena Arsyad (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Agricultural extension officers play a crucial role in increasing knowledge and promoting the adoption of innovations in organic fertilizers among farmers. As educators, innovators, and motivators, agricultural extension officers play a crucial role in promoting the adoption of organic fertilizers among farmers. This study was conducted in the village of Ulapato B from August to October 2024, spanning a period of three months. The objectives of this research are: (1) to analyze the level of adoption of organic fertilizers in corn cultivation during the decision-making process related to innovation among corn farmers, and (2) to examine the diversity of farmers' perceptions regarding the role of agricultural extension officers in the process of adopting organic fertilizer innovations. Primary data were collected through structured interviews with a sample of 77 corn farmers. Data analysis employed frequency distribution and analysis of variance (ANOVA). Frequency distribution was used to categorize the raw data into specific groups for ease of interpretation. At the same time, ANOVA was applied to determine significant differences in farmers' perceptions of the roles of extension officers, namely as educators, innovators, and motivators, based on comparisons of group means. The findings revealed that maize farmers in Ulapato B Village still exhibit low interest in adopting organic fertilizer. The role of extension officers as educators and motivators was perceived positively and contributed significantly to the adoption process. However, their role as innovators was perceived as less effective, particularly in delivering innovations and training related to new technology in organic fertilizer application.